Applying SOBANE Strategy for Risk Management in Museums - Izabela Luiza POP (Communications of International Proceedings, 2022)
One of the main responsibilities of museums is to keep the cultural heritage safe, so as it can be transmitted to future generations in good conditions. For fulfilling this responsibility, museum specialists have to pay a great attention to identifying, monitoring and keeping under control all the risk factors that can produce damages to museum collections. Therefore, the aim of this paper is to present several tools and instruments that can be used by museums for managing risks. The case study conducted at a Romanian art museum revealed how data loggers, statistical analysis and diagnostic analysis helped the museum to improve its conservation activities. Since incorrect temperature and relative humidity were among the factors with the highest risk of generating damages, a special attention was paid to presenting the statistical analysis of microclimate fluctuations. This analysis played a key role in the process of identifying the causes of fluctuations and finding solutions for improvement. The results of the study develop the literature in the field of museum risk management and provide significant information for those museums interested in improving their conservation activities.
Keywords: management; risks; conservation; museums